2023
DOI: 10.3390/life13122270
|View full text |Cite
|
Sign up to set email alerts
|

Mangifera indica L., By-Products, and Mangiferin on Cardio-Metabolic and Other Health Conditions: A Systematic Review

Giulia Minniti,
Lucas Fornari Laurindo,
Nathalia Mendes Machado
et al.

Abstract: Mango and its by-products have traditional medicinal uses. They contain diverse bioactive compounds offering numerous health benefits, including cardioprotective and metabolic properties. This study aimed to explore the impact of mango fruit and its by-products on human health, emphasizing its metabolic syndrome components. PUBMED, EMBASE, COCHRANE, and GOOGLE SCHOLAR were searched following PRISMA guidelines, and the COCHRANE handbook was utilized to assess bias risks. In vivo and in vitro studies have shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…Our feeding test revealed that EEMI significantly reduces food intake in rats, indicating the effects of EEMI on appetite suppression. Previous studies suggest that Mangiferin, a compound found in M. indica, may be responsible for this effect [49]. An acute oral glucose tolerance test (OGTT) showed that EEMI treatment significantly improves blood sugar control in type 2 diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Our feeding test revealed that EEMI significantly reduces food intake in rats, indicating the effects of EEMI on appetite suppression. Previous studies suggest that Mangiferin, a compound found in M. indica, may be responsible for this effect [49]. An acute oral glucose tolerance test (OGTT) showed that EEMI treatment significantly improves blood sugar control in type 2 diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Our feeding test revealed that EEMI significantly reduces food intake in rats, indicating the effects of EEMI on appetite suppression. Previous studies suggest that Mangiferin, a compound found in M. indica, may be responsible for this effect [51]. An acute oral glucose tolerance test (OGTT) showed that EEMI treatment significantly improves blood sugar control in T2DM rats.…”
Section: Discussionmentioning
confidence: 99%
“…These remedies have played an important role in the field, and ongoing research is being conducted to identify potential antimigraine agents [128][129][130]. Herbs and other traditional forms of treatment have been linked to the treatment of conditions such as migraine [131][132][133][134][135][136]. By investigating the properties of these herbs, researchers hope to develop more effective medicines and targeted treatments for various conditions, including migraine.…”
Section: Discussionmentioning
confidence: 99%